Pengaruh kemiringan pada bagian sayap terhadap kelajuan tenggelam tali pemberat alat tangkap pukat cincin - Vonny Olgah Rompas; Alfred Luasunaung; Revols D. CH. Pamikiran; Johnny Budiman; Lawrence J. L. Lumingas; Deiske A. Sumilat; James L. Tumbal (Universitas Sam Ratulangi, 2024)
Purse seine is a tool (gear) used to catch pelagic fish that form a swarm. As with other fishing gear, a purse seine unit consists of a net, a boat, and auxiliary equipment (rollers, lights, echosounders, and so on). Purse seine is a fishing gear classified in the surrounding net group. Purse seine is also known as a ring trawl because it is equipped with a ring that is used as a place to attach the coloring rope which is very important during the operation of the net. Because the net that was originally bagless will form a pocket at the end of the capture operation. The ring trawl itself has a different name in each region in Indonesia, in North Sulawesi it is known as soma pajeko. There are three technical factors that need to be considered for the success of ring trawl fishing, namely: (1) circular speed, (2) speed and depth of sinking ballast rope, and (3) speed of pulling the choir ropeThe speed of sinking is largely determined by the ballast, the type of material, the size of the thread and the size of the net bit, as well as the ratio of the length of the float rope and the ballast rope. The sinking speed of the ballast rope is calculated based on the relationship between the depth and the sinking time of the ballast rope needed. The speed of the ballast can be increased by increasing the weight of the ballast, but it must be considered because it will increase the tension of the net. Ballast weight per meter ballast ropeBut it should be considered because it will add tension to the net. Greater ballast weight per meter ballast rope will add greater sinking speed. The method used in this study is an experimental method, which is a study that looks for the influence of certain variables on other variables under tightly controlled conditions. The analysis in this study consisted of 4 net models with different slope percentages, namely 57%, 75%, 100% and 125% slopes. The results of the analysis showed that the more tilted the wing with a slope of 57%, 75% and 100%, the more the sinking rate of the ballast rope but for a slope of 125% it does not contribute to the speed of sinking 57% slope at a depth of 5.5 meters the required time is 16.37 seconds, 75% slope at a depth of 5.5 meters is 15.16 seconds, 100% slope at a depth of 5.5 meters the time required is 19.84 seconds and 125% slope the time required at a depth of 5.5 meters is 19.88 seconds. The best sinking speed of the four net models that have been made based on existing data is at 75% slope.